(untitled) (Islamic Sciences Journal, 2023)
Praise be to God, and may blessings and peace be upon the Messenger of God, his family, companions, and those who are guided by his guidance. The disease of death is the disease in which death is prevalent and death is often related to it, and it does not affect the capacity of a person in both types of it. It affects the rights of the heirs or the creditors, and the donations of the patient while he is alive take the ruling of a will, and the patient is withheld death from the time of the disease if he has heirs or creditors. After reviewing the jurisprudential issues, it became clear to me that there are certain cases in which the divorced wife does not inherit from her husband the disease of death.